Peculiarities of Glycerol Conversion to Chemicals Over Zeolite-Based Catalysts - Muraza, Oki (Frontiers in Chemistry, 2019)
Many countries have opted to produce biodiesel from vegetable oils for energy security and climate change concerns. Consequently, the availably if glycerol, as a byproduct in biodiesel production is more obvious. The conversions of glycerol to highly-added products have attracted many institutions and companies to explore different routes. As the addition of the second reactant to glycerol may end up with worse exergy calculation, the conversion of glycerol over solid acid catalysts without the second reactant is preferred in this mini review. Glycerol aromatization and glycerol dehydration were focused with an emphasis on recent papers in the past three years. The role of acidity, hydrophilicity-hydrophobicity, zeolite frameworks are highlighted. The presence of water in the glycerol feed affected the stability of the catalysts. Low cost and naturally abundant zeolite and minerals are proposed. Numerous low-cost catalysts such as natural zeolites and natural clays are potentially used for this purpose.